Teaching in Disadvantaged Schools: A Cross-Cultural Exploration of Millennial American and Filipino Teachers (Research, Society and Development, 2019)
Using an interpretive thematic analysis of two American and two Filipino Millennial teachers’ TED Talk and TEDx Talks online video files, this paper aimed to explore the values, beliefs, and worldviews underlying their apparently counter-culture decision to teach in disadvantaged public schools in high poverty rate areas. Through a contextualist lens and using Lloyd Kwast’s model of culture, a cross-cultural comparison of the cultural components of their decisions revealed through their speeches revealed subtle yet fundamental intra-group similarities and differences. Analysis revealed that young American teachers’ values revolve around equity and justice while the Filipinos’ were on children and community welfare. The Americans beliefs centered on the potency of socio-economic opportunities and attitude while the Filipinos believed in the capacity sincere contribution and the highlighting of positive aspects to get things done. Despite these, there appears to be hints of similarities between these two groups until this point. The fundamental difference was revealed in their worldviews. The American worldview was based on the idea and vision of the Enlightenment notions that founded their nation. The Filipinos’ worldviews were based on living with and consequently finding themselves in others. Underneath the counter-culture decision to teach in disadvantaged schools, lies the fundamental cultural differences consisting of rich latent networks and motivations unique to the society and context where they thrive.